Multi-Wall Carbon Nanotubes with NiO and pt as Counter Electrodes for DSSC applications - Ali, Hayder Hasan (University of Thi-Qar Journal of Science, 2023)
NiO-MWCNT was synthesized using the hydrothermal method and used as a low-cost, platinum-free counter electrode for Dye-sensitized solar cells DSSCs. The DSSC based on NiO-MWCNT as a counter electrode achieves a high-power conversion efficiency of 8.53% under a simulated solar illumination of 100 mW cm-2 (AM 1.5). This efficiency is comparable to 7.9% for a DSSC equipped with a Pt counter electrode. Good charge conduction characteristics of the NiO-MWCNT electrode decreases charge loss and boosts the effectiveness of converting light into electrical current. The NiO-MWCNT electrode also increases light absorption and increases the efficiency of converting light energy into electrical energy by enhancing light dispersion within the solar cell. Other advantages of NiO-MWCNT electrodes are low cost and great sustainability. Comparing it to platinum, rare and expensive material, the use of NiO-MWCNT reduces the cost of the solar cell and contributes to environmental sustainability. In addition, the NiO-MWCNT electrode has a high chemical stability, making it more resistant to corrosion and damage in dye solar cell environments. This enhances the lifespan of the cell and ensures its long-term sustainability.